Parody Idioms in the Visual Characteristics of KNIL Andjing NICA Reenactors - Andrian Dektisa (Graduate School of Institut Seni Indonesia Yogyakarta, 2015)
This research is to study the phenomena of wearing military costumes of the past as an alternative ‘means’ of visual communication. People in Indonesia like old military costumes and celebrate them as reenactors (a name for the wearers of old military uniforms) in various social activities that can be categorized into two types of stage, namely main and parallel stage. The main stage is related to learning military history, while parallel stage correlates to euphoria for military fashion. Both stages become an expression of mockery toward postcolonial mimicry and create a cultural postcoloniality that takes place in the contemporary life in Indonesia. This research applies Rose’s visual method that emphasizes the aspect of site image itself by making interviews and getting observation data in the groups of KNIL Andjing NICA reenactors in Surabaya, Bojonegoro, Bandung, and Jakarta. It also applies Barthian semiotics unit analysis.